Leaving home and the chances of being poor: the case of young people in Southern European countries - Lavinia Parisi (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper analyses, for Southern European countries, the link between the poverty status of young people who leave home and the economic status of their family of origin. First we model the poverty status of those who leave home while also accounting for the fact that youths from better-off households are more likely to leave home (a sample selection model). Second we address the time at risk of leaving home using a competing risks duration model. Estimates from both approaches suggest that young people delay leaving home because it may increase their chances of being poor. Moreover both approaches indicate that young people who have left home are more likely to be poor if their family of origin is poor and that differences across countries are not statistically significant.
Keywords: 330